TEACHING ENGLISH FOR ISLAMIC LAW STUDENTS - Sukron Ma’mun (Universitas Negeri Islam Sumatera Utara, 2026)
Teaching English in Islamic higher education requires contextualized approaches that align linguistic competence with students’ disciplinary needs. This study explores the teaching of English for Islamic Law students at UIN Salatiga, focusing on the relevance of English as an academic and professional tool in Islamic legal studies. Employing a qualitative descriptive approach, the research investigates students’ needs, learning challenges, and instructional strategies used in the classroom. The findings indicate that students perceived English as important for accessing international legal and Islamic scholarship; however, they reported low confidence, limited vocabulary mastery, and difficulties relating classroom content to their disciplinary studies. The study also found a mismatch between existing General English materials and the academic needs of Islamic Law students. Both students and lecturers emphasized the need for ESP-oriented instruction incorporating Islamic legal terminology, authentic disciplinary texts, and communicative learning activities. The study recommends integrating Islamic legal content, authentic texts, and communicative learning activities to improve students’ motivation, participation, and learning outcomes. This research contributes to the growing discussion on discipline-specific English instruction in Islamic higher education and highlights the importance of contextualized language learning for future Islamic legal professionals.